Religious Commodification and Deceptive Marketing Go Hand in Hand: The Case of Kampoeng Kurma - Jubei Levianto; Retno Dyah Kusumastuti (Yayasan Riset dan Pengembangan Intelektual, 2023)
Religious commodification, especially Islamic commodification has been rampant in modern times. This phenomenon also emboldens companies with religious symbolism to conduct deceptive marketing, namely The Kampoeng Kurma Group. This research aims to investigate further the integration of religious commodification and deceptive marketing conducted by The Kampoeng Kurma Group. This research utilized a qualitative and descriptive approach through the case study of The Kampoeng Kurma Group's deceptive marketing. The findings of this research are The Kampoeng Kurma Group has benefitted from religious commodification practices. This in turn emboldens The Kampoeng Kurma Group to engage in deceptive marketing by offering its customers high and illogical investment returns, despite its lack of legal documents and business capabilities. This research implies that religious commodification could also bring a negative impact, especially if this practice is coupled with deceptive marketing. Thus, consumers need to be more critical and not easily convinced by the offerings of products that rely on religious commodification, especially if these products use unethical marketing practices such as deceptive marketing.